2022
DOI: 10.1186/s12913-022-08937-9
|View full text |Cite
|
Sign up to set email alerts
|

Health care workers’ need for support from managers during the initial phase of the COVID-19 pandemic

Abstract: Background The COVID-19 pandemic placed great pressure on health care workers and increased the risk of these workers developing mental illness. Effective leadership is essential to prevent mental illness from developing. The study aim was to investigate health care workers’ perceptions of the support given by their managers, their need for such support, and their levels of anxiety during the initial phase of the COVID-19 pandemic. Methods An elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Supportive leadership improves perceived organizational support, employee satisfaction and organizational commitment. 37 , 38 Likewise, effective communication is required to ensure the efficiency of the practice and the safety of the patients. Small communication efforts such as “huddles” was found to be an effective method in keeping up to date during the pandemic, connecting with leadership members, and aided in improving patient care.…”
Section: Discussionmentioning
confidence: 99%
“…Supportive leadership improves perceived organizational support, employee satisfaction and organizational commitment. 37 , 38 Likewise, effective communication is required to ensure the efficiency of the practice and the safety of the patients. Small communication efforts such as “huddles” was found to be an effective method in keeping up to date during the pandemic, connecting with leadership members, and aided in improving patient care.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both COVID-19 waves in India occurred later than they did in Western countries ( 53 ). Therefore, the knowledge gained from experience may have helped health managers and HCWs respond more efficiently, become pandemic-ready, and ease COVID-19-related anxiety ( 54 ). The perception of control over stressful events in HCWs was found to help them cope with and adapt to stressful situations, as well as lower their overall stress.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of 31 studies found that HCWs who reported higher levels of psychological resilience, optimism, and positive coping strategies, such as problem-solving and active coping, were less likely to experience symptoms of anxiety and depression during the pandemic [24]. Additionally, HCWs who reported higher levels of social support from colleagues and supervisors also had lower levels of anxiety and depression [56]. Another study found that HCWs who reported higher levels of emotional intelligence, self-compassion, and mindfulness were less likely to experience burnout and PTSD symptoms during the pandemic [57].…”
Section: Predicting Depressive and Anxiety Symptoms At Follow-upmentioning
confidence: 99%